IMPLEMENTASI PRAKTEK MONOPOLI DI INDONESIA KASUS : LISENSI MC DONALD’S INDONESIA - Tuti Andjarsari (BALANCE: Economic, Business, Management and Accounting Journal, 2010)
Companies generally have several objectives, including the obtaining of profit, sales volume increase, improve and maintain the stock price of survival. Many ways can companies do to maintain the viability of which is to expand marketshare. Expansion of business by increasing marketshare to get to the overseas can be done by means of licenses or franchises (franchises).One of the biggest fast-food restaurant in the world is McDonald's Corporation is expanding its business done by way of granting franchises to consumers who qualify To give this franchise is not easy, where the prospective franchisee is required to attend training which is quite tight and with considerable cost. In 1991, McDonald's Corporation in theUnited States gives a monopoly franchise to Bambang Rachmadi through PT. Bina Nusa Rama (BNR) to manage a McDonald's inIndonesia.As an experienced entrepreneur who founded the Bambang Rachmadi local franchise under the name Toni Jack's, before the expiration of an agreement with McDonald's, this triggers the transfer of McDonald's franchises franchise that bears to the PT Rekso is also the holder of the National Food Sosro brand.Keywords : waralaba, marketshare.